Trust on a Nationwide Scale. - Gratzer, V.
Singapore is a small island nation with roughly 4.5 million inhabitants, but it has a highly developed international economy based on trade, services, and knowledge management. Singapore launched its lofty goals by defining the nationpsilas e-security. Current research in the Singaporean telecommunications and IT security community attempts to model such peer-to-peer ad hoc transactions and leverage the existing standard infrastructure described in this article.
Keywords: IT security community; Singaporean telecommunications; Nations e-security.; Nationwide trust; Peer-to-peer ad hoc transactions